Intra-sphincteric botulinum toxin in the management of functional biliary pain - Menon, Shyam; Holt, Andrew; Farmer, Adam D. (Endoscopy International Open, 2022)
Background and study aims The management of functional biliary-type pain remains a clinical challenge. Intra sphincteric botulinum toxin putatively exerts an anti-spasmodic and anti-nociceptive effect. The objective of this study was to examine the clinical response to intra sphincteric botulinum toxin in patients with functional biliary-type pain.Patients and methods This was a cross-sectional (hypothesis-generating) study of prospectively collected data from patients referred to a tertiary center from 2014 to 2019. The efficacy of ampullary botulinum toxin injection for relief of pain was recorded at post-procedure outpatient review. Opioid analgesia, neuromodulatory medication, and frequency of hospital admissions were recorded.Results A total of 119 consecutive patients (109 women, 10 men, mean age 45 years; range 17–77) underwent 411 intra-sphincteric botulinum toxin injection procedures (mean 2 procedures; range 1–15). A total of 103 patients (87 %) had a significant improvement in pain on post-procedure review and 77 % and 76 % of patients were opioid and admission free, respectively. Of the patients, 59 % were prescribed tricyclic antidepressants (amitriptyline), 18 % duloxetine, 13 % pregabalin, and 3 % mirtazapine. Loss of response with the initial dose of botulinum toxin occurred in 56 % of patients. Pain control was reestablished in 80 % of patients in this cohort following botulinum toxin injection at a higher dose.Conclusions These data suggest that botulinum toxin may improve outcomes in patients with functional biliary pain. Further controlled studies are needed to clarify the role of Botox and neuromodulatory agents.